Improvement at the Operation and Planning Level in the Electrical Workshop of a Mining Machinery Component Repair Center using Forecast Methods and Lean Manufacturing Tools (LACCEI, 2024)
The objective of this study is to reduce the lead time for the repair of components for heavy machinery in the mining industry, through the use of forecasting methods and lean manufacturing tools, taking the electrical workshop of a mining company as a specific example for analysis. The study includes the development of the process diagnosis to identify the critical process, the key problems, their root causes for the validation of the proposed improvement tools, then the development of the Lean Manufacturing methodology and forecast models to improve the process indicators. and finally a technical and economic evaluation to demonstrate the feasibility of the proposal.